THU0307 RESPONSE OF BEHÇET'S REFRACTORY ORAL AND/OR GENITAL ULCERS TO APREMILAST IN COMBINATION VS MONOTHERAPY. NATIONAL MULTICENTER STUDY OF 51 CASES OF CLINICAL PRACTICE. (2nd June 2020) - Herrero Morant, A.; Atienza Mateo, B.; Loricera, J.; Calvo del Rio, V.; Martín-Varillas, J. L.; Graña, J.; Espinosa, G.; Moriano, C.; Pérez Sandoval, T.; Martín Martínez, M.; Diez, E.; García-Armario, M. D.; et al.
Abstract : Background: Apremilast (APR) has demonstrated efficacy in the treatment of oral and/or genital aphthous ulcers in Behçet´s disease (BD). Combination of APR to other disease-modifying anti-rheumatic drugs (DMARDs) has not been assessed. Objectives: To compare the efficacy and safety of APR in monotherapy or combined with DMARDs in refractory BD. Methods: National multicenter open-label study on 51 BD patients with oral and/or genital ulcers refractory to conventional treatment. Results: We included 51 patients (35 women/16 men), mean age 44.7±13.2 years. Before APR, all patients had received several systemic conventional drugs. The main clinical symptoms for starting APR were oral (n=19) and genital (2) aphthous ulcers or both (30). Excluding corticosteroids, colchicine or NSAIDs, APR was given at standard dose of 30 mg twice daily in monotherapy (n=31), or combined with conventional DMARDs in 16 cases (6 azathioprine, 5 methotrexate, 4 hydroxychloroquine, 4 sulfasalazine, 1 dapsone) or with biologic DMARDs in 4 (2 tocilizumab, 1 adalimumab, 1 infliximab). There were not found statistically significant differences in demographic features, previous therapy, clinical manifestations or reported adverse effects. After a median follow-up of 6 [3-12] months, most of the patients experienced improvement of the orogenital ulcers in both groups (89.8% in the first 2 weeks), without statistically significant differences. (TABLE ) Conclusion: APR leads to a rapid and maintained improvement in most patients with refractory BD orogenital ulcers. APR seems as effective and safe in monotherapy as combined. Disclosure of Interests: Alba Herrero Morant: None declared, Belen Atienza Mateo: None declared, J. Loricera: None declared, Vanesa Calvo del Rio Grant/research support from: MSD and Roche, Speakers bureau: Abbott, Lilly, Celgene, Grünenthal, UCB Pharma, José Luis Martín-Varillas Grant/research support from: AbbVie, Pfizer, Janssen and Celgene, Speakers bureau: Pfizer and Lilly, Jenaro Graña: None declared, Gerard Espinosa: None declared, Clara Moriano: None declared, Trinidad Pérez Sandoval: None declared, Manuel Martín Martínez: None declared, Elvira Diez: None declared, María Dolores García-Armario: None declared, Esperanza Martínez: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Patricia Moya Alvarado: None declared, Francisca Sivera: None declared, Jaime Calvo Grant/research support from: Lilly, UCB, Consultant of: Abbvie, Jansen, Celgene, Isabel de la Morena: None declared, Francisco Ortiz Sanjuán: None declared, José Andrés Román Ivorra: None declared, Ana Pérez Gómez: None declared, Sergi Heredia: None declared, Alejandro Olive: None declared, Águeda Prior: None declared, Carolina Díez: None declared, Juanjo J Alegre-Sancho Consultant of: UCB, Roche, Sanofi, Boehringer, Celltrion, Paid instructor for: GSK, Speakers bureau: MSD, GSK, Lilly, Sanofi, Roche, UCB, Actelion, Pfizer, Abbvie, Novartis, D Ybáñez-García Speakers bureau: Lilly, Roche, Sanofi, Ángels Martínez-Ferrer: None declared, J. Narváez: None declared, Ignasi Figueras: None declared, Ana Isabel Turrión: None declared, Susana Romero-Yuste: None declared, Pilar Trénor: None declared, Soledad Ojeda Speakers bureau: AMGEN, LILLY, GEBRO, Miguel Á. González-Gay Grant/research support from: AbbVie, MSD and Roche, Speakers bureau: AbbVie, MSD and Roche, Ricardo Blanco Grant/research support from: Abbvie, MSD and Roche, Consultant of: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen and MSD, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Lilly and MSD